2002
DOI: 10.1021/jf0114482
|View full text |Cite
|
Sign up to set email alerts
|

Honey from Plants Containing Pyrrolizidine Alkaloids:  A Potential Threat to Health

Abstract: Following scientific risk assessments, several countries have imposed strict regulations on herbal medicines containing 1,2-dehydro-pyrrolizidine alkaloids. Using published data on the plants used in honey production, pyrrolizidine alkaloid-containing plants are shown in this review to represent a significant source of honey worldwide. This observation, honey consumption data, reported levels of pyrrolizidine alkaloids in honeys, and consideration of tolerable exposure levels determined for pyrrolizidine alkal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
1
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(100 citation statements)
references
References 39 publications
2
87
1
7
Order By: Relevance
“…Honey was shown to be another source of PA exposure; here it seems that the contamination may be due to the plant pollen, which is rich in PAs, being transferred by bees into the honey [Deinzer, Thomson, et al, 1977;Culvenor, Edgar, et al, 1981;Roeder, 1995Roeder, , 2000Edgar, Roeder, et al, 2002;Beales, Betteridge, et al, 2004;Boppré, Colgate, et al, 2005;Betteridge, Cao, et al, 2005]. Eggs from poultry exposed to PAs in PA-contaminated grain were also shown to be a possible source of PA exposure for humans [Edgar, Smith, 1999].…”
Section: Helmut Wiedenfeldmentioning
confidence: 99%
“…Honey was shown to be another source of PA exposure; here it seems that the contamination may be due to the plant pollen, which is rich in PAs, being transferred by bees into the honey [Deinzer, Thomson, et al, 1977;Culvenor, Edgar, et al, 1981;Roeder, 1995Roeder, , 2000Edgar, Roeder, et al, 2002;Beales, Betteridge, et al, 2004;Boppré, Colgate, et al, 2005;Betteridge, Cao, et al, 2005]. Eggs from poultry exposed to PAs in PA-contaminated grain were also shown to be a possible source of PA exposure for humans [Edgar, Smith, 1999].…”
Section: Helmut Wiedenfeldmentioning
confidence: 99%
“…Recent studies have demonstrated significant amounts of PAs in floral pollen of PA-plants (Boppré et al 2008;Kempf et al 2010b). Therefore, PA pollen is discussed as the only source or as major contributor to PA-contamination of honey (Edgar et al 2002;Boppré et al 2005;Kempf et al 2010a). To date, it is unknown, whether the PA-content found in honey is an artifact of the preceding sample preparation (including To address these questions we added defined amounts of floral PA pollen derived from…”
Section: Pa Carry-over From Pa-pollen Into Honeymentioning
confidence: 99%
“…Chronic ingestion of PA-containing plants and contaminated hay, straw or silage, causes livestock poisoning (Cheeke, 1988;Wiedenfeld and Edgar, 2011). In humans, exposure to PAs contained in herbal teas, medicines, contaminated cereals, pollen and honey has been related to acute and chronic liver toxicity, such as the veno-occlusive disease, especially in children (Edgar et al, 2002;Kempf et al, 2010;Molyneux et al, 2011;Wiedenfeld and Edgar, 2011). The role of PAs as plant chemical defenses against phytophagous insects has been widely documented (Hartmann, 1999).…”
Section: Introductionmentioning
confidence: 99%